Protosappanin-B suppresses human melanoma cancer cell growth through impeding cell survival, inflammation and proliferative signaling pathways. (November 2022) - Wang, Shuang; Jiang, Kejiao; Muthusamy, Rajasekar; Kalaimani, Saravanan; Selvababu, Azhagu Pavithra; Balupillai, Agilan; Narenkumar, Jayaraman; Jeevakaruniyam, Sathiya jeeva
Abstract: This study evaluates protosappanin B's (PSB) role in inflammation, proliferation, and subsequent apoptosis of human melanoma A875 cells. The cell lines were treated with PSB (15 and 20 μM) for 24 h of incubation mediated cytotoxicity was assessed by MTT assay; ROS was studied by flow cytometry. PSB treatment mediated nuclear fragmentation and apoptotic morphological features were analyzed by AO, EtBr, PI, and DAPI stainings. The mRNA and protein expression of inflammatory, proliferation, cell survival and apoptosis were studied by RT-PCR and western blotting. PSB (15 and 20 μM) treatment with A875 produces cytotoxicity associated with nuclear fragmentation, and apoptotic changes were observed. PSB inhibits inflammatory proteins (TNF-α, NF-κB, COX-2, IL-6, iNOS, and VEGF) in A875 cells. Furthermore, PSB induces pro-apoptotic protein expressions i.e . Bax, caspase-3; inhibiting anti-apoptotic, cell proliferative proteins (cyclin-D1, Bcl-2, c-Myc, and survivin) in A875 cells. The p-PI3K, p-AKT, and p-GSK-3β contribute to oncogenic progression; hence, inhibition of these signaling events is considered a significant target for the treatment of melanoma. This study observed that PSB treatment magnificently inhibited the p-PI3K, p-AKT, and p-GSK-3β in A875 cells. Thus, PSB inhibits inflammation, proliferation, and survival; promotes apoptosis by suppressing PI3K, AKT, and GSK-3β in human melanoma cancer. Graphical Abstract: 1. PSB treatment inhibits inflammatory proteins and proliferative proteins in A875 cells. Furthermore, PSB induces pro-apoptotic gene expressions such as Bax, and caspase-3 and inhibits anti-apoptotic or cell proliferative genes such as cyclin-D1, Bcl-2, c-Myc, and survivin expressions by impeding the expression of the phosphorylated form of PI3K, AKT, and GSK-3β in A875 cells. ga1 Highlights: Protosappanin-B concern as a natural drug that has numerous biological activity. Protosappanin-B inhibits inflammation and proliferation in A875 cells. Protosappanin-B inhibits melanoma cancer via suppression of PI3K/AKT expressions.